Heart Failure Clinic: A Practical Guide for Health Practitioners in Hospitals - Sidhi Laksono (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Heart failure is still the leading cause of mortality and morbidity in healthcare in the world. Although the development of the latest drugs and therapeutic devices for heart failure is growing, the life expectancy of patients with heart failure is still low. This is because the hospital has not developed a special heart failure clinic consisting of cross-sectional experts. This heart failure clinic will provide therapy according to heart failure guidelines and will discuss with the patient what therapy is suitable for his condition. This clinic is expected to be a link with advances in technology and medical therapy to improve the quality of life of heart failure patients.